Solar Rebound - The Unintended Consequences of Subsidies - Nicolas Boccard; Axel Gautier (Center for Economic Studies and ifo Institute (CESifo), 2019)
Many jurisdictions use net metering to record the power exchange between solar photovoltaic panels and the grid, thus valuing home production at the electricity retail rate. However, if over the billing period, production exceeds consumption, the surplus remains freely available for consumption. In Wallonia (Belgium), this system was combined with generous subsidies for solar panels that encouraged households to set-up large installations, possibly exceeding their consumption needs. In this context, we test for a possible rebound effect. Based on a large sample of residential PV installations, we observe that a large proportion of households oversized their installation to benefit from the subsidies and, later ended-up consuming most of their excess production. The effect is econometrically highly significant. There are thus evidence of a strong increase in energy consumption by residential PV owners, that runs counter the original policy design.
Keywords: C51; Q48; Q58; Q41; Q42; 330; rebound effect; solar PV; net metering